2014
DOI: 10.5050/ksnve.2014.24.4.339
|View full text |Cite
|
Sign up to set email alerts
|

Floor Impact Sound Pressure Level Characteristics by the Change of Reverberation Time in Mock-up Test Rooms

Abstract: Floor impact sound in high-rise apartment building became one of social problems. A lot of civil complaints on floor impact sound occur continuously and the number of disputes between neighbors in small and aged apartment buildings is increasing. Interests on heavy-weight impact sound pressure level measurement and evaluation method is increased. Previous study reported that heavy-weight impact sound level was changed by the sound field condition of receiving reverberation chamber. In this study, heavy-weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The floor impact sound generated in apartments considerably affects the comfort of residents, as indicated by research across Korea, Japan, and Europe, among other countries [1][2][3] Particularly, most Korean people live in apartments built with concrete and their in-door lifestyle is that they live in bare feet. This lifestyle and structure showed that with the amplification of impact sounds, which had low frequencies, and the reduction of impact sound, it was made more difficult because of the propagation characteristics of low frequency [4][5][6][7][8][9]. Specifically, these sounds can adversely influence the physical and psychological health of the residents and lead to property-related issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The floor impact sound generated in apartments considerably affects the comfort of residents, as indicated by research across Korea, Japan, and Europe, among other countries [1][2][3] Particularly, most Korean people live in apartments built with concrete and their in-door lifestyle is that they live in bare feet. This lifestyle and structure showed that with the amplification of impact sounds, which had low frequencies, and the reduction of impact sound, it was made more difficult because of the propagation characteristics of low frequency [4][5][6][7][8][9]. Specifically, these sounds can adversely influence the physical and psychological health of the residents and lead to property-related issues.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, these sounds can adversely influence the physical and psychological health of the residents and lead to property-related issues. Although many researchers have examined floor impact sounds [4][5][6][7][8][9] and the corresponding influence of floor structures of public residences [10][11][12][13] using several evaluation indices [14][15][16][17][18], the problem of floor impact sounds remains to be solved. In this context, it is necessary to accurately predict floor impact sounds, especially in the Korean environment, as a relevant law named floor impact sound post-check system, and is expected to be enforced in July 2022.…”
Section: Introductionmentioning
confidence: 99%